Ecological and economic profile of cities: on the way to sustainable development - Nazarenko, V.; Voytovich, О. (Land Management, Cadastre and Land Monitoring, 2025)
Ecology has become an urgent global problem for modern metropolises. Cities seek to balance their economic growth and preserve the state of the environment. One of the programs that more and more cities are implementing at the municipal level is the sustainable development program (based on the Paris Climate Agreement). This study presents cities' environmental and economic profiles through the prism of their economy. The main focus of the work is on waste management, reducing harmful emissions, and increasing the economic development of cities. The principles of integration of a modern green city were worked out and analyzed to determine the optimal strategies for its development.  Such a strategy should synchronize the economic activities of the city with the goals of the sustainable development program.A study has been carried out using a multi-disciplinary approach to collecting and analyzing quantitative and qualitative data on the life of cities. With the help of statistical modeling, general social and economic indicators were assessed, and the results of the calculation of important environmental data were presented. Among the data processed, we can highlight the general programs of urban budget expenditures, waste management indicators, and emission profiles. The following three cities were selected to conduct the study and test the results: Kyiv, Paris, and New York. The information on the leading socio-economic indicators of their development was analyzed. The authors considered the norms of the current legislation related to cities' ecology and land use. This made it possible to provide an assessment of the implementations and plans of sustainable development programs. This will allow us to further assess the impact of the sustainable development program until 2035 on the current (annual) level of economic development.Based on the studies, the selected cities successfully implemented sustainable development programs based on the climate agreement in stages. Green areas are expanding in selected cities, and investment in development programs and support for the renewable energy initiative continues. It can be confidently stated that at the local level, harmful emissions have been reduced, and the effectiveness of waste management programs has been increased. For example, Paris and New York allocate significant portions of their budgets to sustainability programs, demonstrating effective alignment between investments in environmental conservation programs and the sustainability of economic development. Despite limited resources, the city of Kyiv is demonstrating progress in modernizing waste disposal systems and adopting EU environmental regulations.The economic development of cities can harmonize harmoniously with implementing environmental programs. First, this is due to targeted investment programs and the adaptation of new urban programs related to the environment. In the future, it is advisable to develop mechanisms of cooperation between municipal authorities, public organizations, and private businesses to solve environmental problems and overcome the negative impact of their consequences. This makes it possible to create a roadmap for effective city management. Such city development programs will improve their environmental and economic profiles, supporting the global pursuit of sustainable development. Keywords: urban economic, green city, waste management, harmful emissions, economic development.
Keywords: urban economic; green city; waste management; harmful emissions; economic development